Climate Smart Cocoa in Ghana Towards climate resilient production at scale - Bunn, Christian; Fernández Kolb, Pablo; Asare, Richard; Lundy, Mark M. (2019)
Climate Smart Cocoa (CSC) is not only about avoiding future losses but also about mitigating greenhouse gas (GHG) emissions and improving the livelihoods of farmers by increasing the productivity and resilience of their farms. The current state of cocoa production in Ghana has significant leeway to become more forward-looking and productive. Cocoa farms in Ghana are vulnerable to an array of climate-related risks: the Harmattan wind, droughts, storms, flooding. Climate change is projected to increase the occurrence of such extreme events, as well as induce more gradual changes to cocoa farming suitability via higher average temperatures and more erratic rainfall. Whether sudden or gradual, production needs to be resilient to these changes.